Binder composition for electrochemical element electrode, slurry composition for electrochemical element electrode, electrode for electrochemical element, and electrochemical element

By using a binder composition with a granular polymer having a specified shell core structure and a polymer with a specific property, the problem of insufficient peel strength and depowder resistance of the electrochemical element electrode composite material layer is solved, and the electrochemical is improved Component magnification characteristics and stability.

CN112262488BActive Publication Date: 2025-01-03ZEON CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980038596.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-06-29
Filing Date
2019-06-24
Publication Date
2025-01-03
Estimated Expiration
2039-06-24

AI Technical Summary

Technical Problem

The peel strength and depowder resistance of the existing electrochemical component electrode composite material layers are insufficient, resulting in a degradation of electrochemical component performance, especially in fast charging and discharging applications.

Method used

Using a binder composition containing a granular polymer having a specified shell core structure and a polymer of a specific property, the peel strength and detachment resistance of the electrode composite material layer are improved by adjusting the glass transition temperature and viscosity of the polymer. Pinky.

Benefits of technology

The peel strength and depowder resistance of the electrode composite material layer are significantly improved, the magnification characteristics of the electrochemical components are enhanced, and the stability of the electrode composite material layer under high density and high surface density conditions is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002820601190000381
    Figure BDA0002820601190000381
Patent Text Reader

Abstract

The object of the present invention is to provide an electrochemical element electrode binder composition that can form an electrode composite material layer with excellent peel strength and resistance to powder removal, and can enable the electrochemical element to exert high-rate characteristics. The electrochemical element electrode binder composition of the present invention is characterized in that it comprises a binder and an organic solvent, the binder comprises a granular polymer A and a polymer B, the granular polymer A has a core-shell structure, the core-shell structure has a core and a shell covering at least a portion of the outer surface of the core, the polymer constituting the shell has a glass transition temperature of more than 50°C and less than 20°C, and the polymer B is mixed with the organic solvent at a concentration of 8% by mass to obtain a mixed solution at a shear rate of 1s ‑1 The viscosity at that time is 100 mPa·s or more and 10000 mPa·s or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a binder composition for an electrochemical element electrode, a slurry composition for an electrochemical element electrode, an electrochemical element electrode, and an electrochemical element. Background Art

[0002] Electrochemical devices such as lithium-ion secondary batteries and electric double layer capacitors are used in a wide range of applications because they are small, lightweight, have high energy density, and can be repeatedly charged and discharged.

[0003] Here, for example, the electrode for lithium ion secondary battery generally has a current collector and an electrode composite material layer (positive electrode composite material layer or negative electrode composite material layer) formed on the current collector. Moreover, the electrode composite material layer can be formed by, for example, applying a slurry composition including an electrode active material, a binder composition containing a binding material, etc. on the current collector and drying the applied slurry composition.

[0004] Therefore, in recent years, attempts have been made to improve the binder composition used to form the electrode composite material layer in order to further improve the performance of the electrochemical device.

[0005] For example, in Patent Document 1, the following scheme is proposed: by using a secondary battery electrode binder composition comprising a first particulate polymer having a core-shell structure, the core-shell structure having a core portion and a shell portion partially covering the outer surface of the core portion, a secondary battery having excellent rate characteristics and cycle characteristics is produced. Here, Patent Document 1 discloses the following: the glass transition temperature of the polymer constituting the core portion is preferably above -60°C and below -15°C, and the glass transition temperature of the polymer constituting the shell portion is preferably above 40°C and below 200°C.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: International Publication No. 2016 / 035286. Summary of the invention

[0009] Problem that the invention aims to solve

[0010] However, from the viewpoint of improving the performance of electrochemical devices, the electrode composite layer is required to have excellent peel strength (adhesion strength between components in the electrode composite layer and adhesion strength between the electrode composite layer and the current collector).

[0011] In addition, in the manufacturing process of the electrochemical element, the electrode before being immersed in the electrolyte is sometimes cut to a desired size. At this time, if the adhesion of the binding material contained in the electrode composite material layer is insufficient, the electrode active material constituting the electrode composite material layer will fall off from the electrode composite material layer (hereinafter, also referred to as "de-powdering"), which will cause a decrease in the performance of the electrochemical element under the operating environment of the electrochemical element. Therefore, it is also required that the electrode composite material layer is not easy to de-powder, that is, excellent de-powdering resistance is required.

[0012] Furthermore, when used in applications requiring rapid charging and discharging, such as electric tools and electric vehicles, electrochemical devices are required to exhibit high rate characteristics.

[0013] Here, in recent years, in order to increase the capacity of electrochemical devices, it has been required to increase the density and surface density of electrode composite material layers.

[0014] However, in the case of attempting to use a slurry composition comprising the above-mentioned prior art binder composition to form a high-density and high-surface-density electrode composite material layer, and to make the electrochemical element high-capacity, the peel strength and resistance to powder removal of the electrode composite material layer, and the rate characteristics of the electrochemical element will become insufficient. Therefore, for the slurry composition comprising the above-mentioned prior art binder composition, even in the case of high-density and high-surface-density, there is still room for improvement in terms of making the obtained electrode composite material layer play an excellent peel strength and resistance to powder removal, and improving the rate characteristics of the electrochemical element.

[0015] Therefore, an object of the present invention is to provide a binder composition for electrochemical element electrodes and a slurry composition for electrochemical element electrodes that can form an electrode composite material layer having excellent peel strength and powder removal resistance and enabling an electrochemical element to exhibit high rate characteristics.

[0016] Another object of the present invention is to provide an electrode for an electrochemical device having an electrode composite material layer which is excellent in peel strength and resistance to powder removal and which enables the electrochemical device to exhibit high rate characteristics.

[0017] Furthermore, an object of the present invention is to provide an electrochemical device having the electrode and having high rate characteristics.

[0018] Solutions for solving problems

[0019] The present inventors have conducted in-depth research for the purpose of solving the above-mentioned problems. Then, the present inventors found that if a binder composition for an electrochemical element electrode comprising the following binder material and an organic solvent is used, the binder material comprising a granular polymer having a core-shell structure with a specified shell portion and a polymer having specified properties, an electrode composite material layer having excellent peel strength and resistance to powder removal and enabling the electrochemical element to exhibit high rate characteristics can be formed, thereby completing the present invention.

[0020] That is, the present invention aims to advantageously solve the above-mentioned problems. The binder composition for an electrochemical element electrode of the present invention is characterized in that it comprises a binder material and an organic solvent, the binder material comprises a granular polymer A and a polymer B, the granular polymer A has a core-shell structure, the core-shell structure comprises a core portion and a shell portion covering at least a portion of the outer surface of the core portion, the glass transition temperature of the polymer constituting the shell portion is above -50°C and below 20°C, and the mixed solution obtained by mixing the polymer B with the organic solvent at a concentration of 8% by mass at a shear rate of 1s -1 The viscosity is 100 mPa·s or more and 10000 mPa·s or less. In this way, the binder contains a granular polymer A having a core-shell structure with a shell portion having the above-specified glass transition temperature and a polymer B having the above-specified properties. If a binder composition for an electrochemical element electrode containing the binder and an organic solvent is used, an electrode composite material layer having excellent peel strength and resistance to powder removal and enabling the electrochemical element to exhibit high rate characteristics can be formed.

[0021] In addition, the glass transition temperature and the shear rate of 1s -1 The "viscosity at 50°C" can be measured by the method described in the Examples of this specification.

[0022] Here, the electrochemical element electrode binder composition of the present invention preferably contains the polymer B in the binder material in a ratio of 60% by mass or more and 95% by mass or less. If the polymer B in the binder material is within the above-specified range, the peel strength and the resistance to powder removal of the obtained electrode composite material layer can be further improved, and the rate characteristics of the electrochemical element can be further improved.

[0023] In addition, the electrochemical element electrode binder composition of the present invention preferably contains cyano-containing monomer units in a ratio of 60% by mass or more of the polymer B. If the polymer B contains cyano-containing monomer units in a ratio greater than the above-mentioned prescribed ratio, the peel strength and resistance to powder removal of the obtained electrode composite material layer can be further improved, and the rate characteristics of the electrochemical element can be further improved.

[0024] Furthermore, the electrochemical element electrode binder composition of the present invention preferably comprises a cross-linking monomer unit in a polymer constituting the core portion at a ratio of 0.01 mass % or more and 4.00 mass % or less. If the polymer constituting the core portion comprises a cross-linking monomer unit in the above-specified ratio, the peel strength and the resistance to powder removal of the obtained electrode composite material layer can be further improved, and the rate characteristics of the electrochemical element can be further improved.

[0025] In addition, the electrochemical device electrode binder composition of the present invention is preferably a mixture of the above-mentioned binder material at a concentration of 8 mass % and the above-mentioned organic solvent at a shear rate of 1 s -1 When the viscosity is 5000 mPa·s or more. When the above-mentioned adhesive material is mixed with the above-mentioned organic solvent at a concentration of 8 mass %, the mixed liquid is subjected to a shear rate of 1s -1 When the viscosity is equal to or higher than the above-specified value, the peel strength and the resistance to powder falling of the obtained electrode composite material layer can be further improved, and the rate characteristics of the electrochemical device can be further improved.

[0026] Furthermore, the present invention aims to advantageously solve the above-mentioned problems, and the electrochemical element electrode slurry composition of the present invention is characterized in that it contains an electrode active material and any of the above-mentioned electrochemical element electrode binder compositions. As such, if a slurry composition for an electrochemical element electrode containing an electrode active material and any of the above-mentioned electrochemical element electrode binder compositions is used, an electrode composite material layer having excellent peel strength and resistance to powder removal and enabling the electrochemical element to exhibit high rate characteristics can be formed.

[0027] In addition, the present invention aims to advantageously solve the above-mentioned problems, and the electrode for electrochemical element of the present invention is characterized in that it has an electrode composite material layer formed using the above-mentioned slurry composition for electrochemical element electrode. Such an electrode for electrochemical element has an electrode composite material layer that is excellent in peel strength and resistance to powder removal and can enable the electrochemical element to exhibit high-rate characteristics.

[0028] The present invention aims to solve the above problems, and the electrochemical device of the present invention is characterized in that it has the above-mentioned electrode for electrochemical device electrode. The electrochemical device of the present invention has an electrode composite material layer with excellent peel strength and powder removal resistance, and can exhibit high rate characteristics.

[0029] Effects of the Invention

[0030] According to the present invention, it is possible to provide a binder composition for electrochemical element electrodes and a slurry composition for electrochemical element electrodes that can form an electrode composite material layer having excellent peel strength and powder removal resistance and enabling an electrochemical element to exhibit high rate characteristics.

[0031] Furthermore, according to the present invention, it is possible to provide an electrode for an electrochemical device having an electrode composite material layer which is excellent in peel strength and resistance to powder removal and which enables the electrochemical device to exhibit high rate characteristics.

[0032] Furthermore, according to the present invention, it is possible to provide an electrochemical device having the electrode and capable of exhibiting high-rate characteristics. DETAILED DESCRIPTION

[0033] Hereinafter, embodiments of the present invention will be described in detail.

[0034] Here, the electrochemical element electrode binder composition of the present invention (hereinafter, sometimes referred to as "binder composition"). It can be used when preparing a slurry composition for electrochemical element electrodes (hereinafter, sometimes referred to as "slurry composition".). Moreover, the slurry composition for electrochemical element electrodes prepared using the binder composition for electrochemical element electrodes of the present invention can be used when manufacturing electrodes of electrochemical elements such as lithium-ion secondary batteries. Furthermore, the electrode for electrochemical element of the present invention (hereinafter, sometimes referred to as "electrode") is characterized in that it has an electrode composite material layer formed using the slurry composition for electrochemical element electrodes of the present invention. In addition, the electrochemical element of the present invention is characterized in that it has an electrode for electrochemical element of the present invention.

[0035] (Binder composition for electrochemical element electrodes)

[0036] The binder composition for electrochemical element electrodes of the present invention comprises a binder and an organic solvent. Moreover, the binder is characterized by comprising a granular polymer A having a core-shell structure with a shell portion having a glass transition temperature in a specified range and a polymer B having specified properties. Furthermore, the binder composition for electrochemical element electrodes of the present invention may contain any other components in addition to the binder and the organic solvent.

[0037] Here, the electrochemical element electrode binder composition of the present invention comprises a binder material and an organic solvent, and the binder material contains a granular polymer A having a core-shell structure with a glass transition temperature in the shell portion of the above-mentioned specified range and a polymer B having the above-mentioned specified properties, so if a slurry composition comprising the binder composition of the present invention is used, then even in the case of forming a high-density and high-surface-density electrode composite material layer, it is possible to suppress the reduction of peel strength and resistance to powdering. Therefore, it is possible to form an electrode composite material layer having excellent peel strength and resistance to powdering and enabling an electrochemical element to exert high-rate characteristics. Although the reason is not yet clear, it is speculated as follows.

[0038] That is, it is speculated as follows: by making the binder composition include a granular polymer A of a core-shell structure having a shell portion with a prescribed glass transition temperature, when a slurry composition containing the binder composition is used to form an electrode composite material layer, the bonding area of ​​the granular polymer A after electrode pressing increases, so it is possible to give the obtained electrode composite material layer excellent peel strength and resistance to de-powdering. Furthermore, it is speculated as follows: by making the binder composition include a polymer B of a prescribed property, a suitable viscosity is given to the slurry composition containing the binder composition, thereby improving the coating property of the slurry composition, and giving the obtained electrode composite material layer excellent peel strength and resistance to de-powdering. In addition, it is speculated as follows: by including the polymer B in the binder composition, the electrode active material, etc. can be added without sedimentation in the slurry composition at a sufficient solid content concentration, so that the obtained electrochemical element with an electrode composite material layer can exert high rate characteristics.

[0039] <Bonding material>

[0040] The binder is a component that keeps the components contained in the electrode composite layer from being separated from the electrode composite layer in an electrode manufactured by forming an electrode composite layer on a current collector using a slurry composition containing the binder composition. Here, the binder composition of the present invention contains a granular polymer A having a core-shell structure with a shell portion having a glass transition temperature in a specified range and a polymer B having specified properties.

[0041] <<Granular polymer A>>

[0042] The particulate polymer A is a component that can impart excellent peel strength and powder removal resistance to an electrode composite material layer formed using the binder composition.

[0043] [Structure of granular polymer A]

[0044] Here, the particulate polymer A has a core-shell structure having a core and a shell covering at least a portion of the outer surface of the core. That is, the shell of the particulate polymer A may cover a portion of the outer surface of the core or the entire outer surface of the core.

[0045] In addition, as long as the desired effect is not significantly impaired, the granular polymer A may have any structural element other than the above-mentioned core and shell. Specifically, for example, the granular polymer A may have a part formed by a polymer different from the core inside the core. When citing a specific example, the seed particles used in the case of manufacturing the granular polymer A by the seed polymerization method may remain inside the core. However, from the viewpoint of significantly exerting the desired effect, it is preferred that the granular polymer A only has a core and shell.

[0046] - Nuclear Department -

[0047] =Composition=

[0048] The polymer constituting the core portion is not particularly limited, and may include, for example, an acid group-containing monomer unit, a (meth)acrylic acid ester monomer unit, and a crosslinking monomer unit.

[0049] In addition, in this specification, "comprising a monomer unit" means "a polymer obtained by using the monomer contains a repeating unit derived from the monomer".

[0050] ==Acid group-containing monomer unit==

[0051] The acid group-containing monomer unit is a repeating unit derived from an acid group-containing monomer. If the polymer constituting the core portion contains the acid group-containing monomer unit, excellent adhesive force can be exerted, so the obtained electrode composite material layer can exert more excellent peel strength.

[0052] Here, examples of the acid group-containing monomer that can form the acid group-containing monomer unit include a monomer having a carboxylic acid group, a monomer having a sulfonic acid group, and a monomer having a phosphoric acid group.

[0053] Examples of the carboxylic acid group-containing monomer include monocarboxylic acids and derivatives thereof, dicarboxylic acids and anhydrides thereof, and derivatives thereof.

[0054] Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid.

[0055] Examples of the monocarboxylic acid derivative include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid.

[0056] Examples of the dicarboxylic acid include maleic acid, fumaric acid, and itaconic acid.

[0057] Examples of the dicarboxylic acid derivatives include maleic acid monoesters such as methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.

[0058] Examples of the anhydride of dicarboxylic acid include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.

[0059] Furthermore, as the carboxylic acid group-containing monomer, an acid anhydride that generates a carboxyl group by hydrolysis can also be used.

[0060] Examples of the sulfonic acid group-containing monomer include styrene sulfonic acid, vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)allyl sulfonic acid, 3-allyloxy-2-hydroxypropane sulfonic acid, and 2-acrylamido-2-methylpropane sulfonic acid.

[0061] In addition, in this specification, "(meth)allyl group" means an allyl group and / or a methallyl group.

[0062] Furthermore, examples of the phosphoric acid group-containing monomer include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.

[0063] In addition, in the present invention, "(meth)acryloyl" means acryloyl and / or methacryloyl.

[0064] These acid group-containing monomers can be used alone or in combination with two or more. And, among these acid group-containing monomers, from the viewpoint of further improving the peel strength of the obtained electrode composite material layer, preferably carboxylic acid group-containing monomers, wherein acrylic acid, methacrylic acid, itaconic acid, maleic acid and fumaric acid are preferably used, and methacrylic acid is more preferably used.

[0065] Moreover, when all repeating units in the polymer constituting the core portion are set to 100.00 mass %, the containing ratio of the acidic monomeric unit in the polymer constituting the core portion is preferably more than 1.00 mass %, more preferably more than 1.50 mass %, more preferably more than 2.00 mass %, particularly preferably more than 3.00 mass %, most preferably more than 4.00 mass %, preferably less than 10.00 mass %, more preferably less than 8.00 mass %, further preferably less than 6.00 mass %, particularly preferably less than 5.00 mass %. By making the containing ratio of the acidic monomeric unit within the above range, the peel strength of the electrode composite material layer formed using the slurry composition comprising the binder composition can be further improved.

[0066] ==Crosslinking monomer unit==

[0067] The cross-linkable monomer unit is a repeating unit from a cross-linkable monomer. A cross-linkable monomer is a monomer that can form a cross-linked structure when polymerized. Moreover, if the polymer constituting the core portion contains a cross-linkable monomer unit, the peel strength and resistance to powder removal of the obtained electrode composite material layer can be further improved, and the electrolyte swelling degree of the granular polymer A can be reduced. Therefore, the void portion of the electrode composite material layer caused by excessive swelling of the granular polymer A in the electrolyte can be suppressed to reduce, and the internal resistance of the electrochemical element can be reduced, thereby further improving the rate characteristics of the electrochemical element. As an example of a cross-linkable monomer, a monomer having more than two reactive groups per molecule can be cited.

[0068] More specifically, as the crosslinkable monomer, a polyfunctional ethylenically unsaturated carboxylic acid ester monomer having two or more ethylenically unsaturated bonds can be mentioned.

[0069] Examples of the difunctional ethylenically unsaturated carboxylic acid ester monomer having two ethylenically unsaturated bonds in the molecule include allyl acrylate, allyl methacrylate, ethylene diacrylate, ethylene dimethacrylate, 2-hydroxy-3-acryloxypropyl methacrylate, polyethylene glycol diacrylate, propoxylated ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloxyethoxy)phenyl]fluorene, propoxylated bisphenol A diacrylate, tricyclodecane dimethanol diacrylate, 1,10-decanediol diacrylate, 1,6-hexanediol Diacrylate, 1,9-nonanediol diacrylate, polypropylene glycol diacrylate, polypropylene glycol dimethacrylate, polybutylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, ethoxylated bisphenol A dimethacrylate, tricyclodecane dimethanol dimethacrylate, 1,10-decanediol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, neopentyl glycol dimethacrylate, ethoxylated polypropylene glycol dimethacrylate and glycerol dimethacrylate, etc.

[0070] Examples of the trifunctional ethylenically unsaturated carboxylic acid ester monomer having three ethylenically unsaturated bonds in the molecule include ethoxylated isocyanuric acid triacrylate, ε-caprolactone-modified tri(2-acryloyloxyethyl)isocyanurate, ethoxylated glycerol triacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate.

[0071] Examples of the tetrafunctional or higher-functional ethylenically unsaturated carboxylic acid ester monomer having four or more ethylenically unsaturated bonds in the molecule include ditrimethylolpropane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, pentaerythritol tetraacrylate, dipentaerythritol polyacrylate, and dipentaerythritol hexaacrylate.

[0072] Among them, from the viewpoint of further improving the peel strength and powder removal resistance of the obtained electrode composite material layer and the rate characteristics of the electrochemical element, it is preferred to use allyl methacrylate (2-functional), ethylene glycol dimethacrylate (2-functional), trimethylolpropane triacrylate (3-functional) and ethoxylated pentaerythritol tetraacrylate (4-functional), and allyl methacrylate is particularly preferred.

[0073] Moreover, all repeating units contained in the polymer constituting the core portion are set to 100.00% by mass, and the content ratio of the crosslinkable monomer unit in the polymer constituting the core portion is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, preferably 4.00% by mass or less, more preferably 1.00% by mass or less, and more preferably 0.40% by mass or less. By making the content ratio of the crosslinkable monomer unit in the polymer constituting the core portion to be above the above lower limit, the peel strength and the resistance to powder removal of the obtained electrode composite material layer can be further improved, and the electrolyte swelling degree of the binding material can be further reduced, so the internal resistance of the electrochemical element with the obtained electrode composite material layer can be further reduced, and the rate characteristics of this electrochemical element can be further improved. In addition, by making the content ratio of the crosslinkable monomer unit in the polymer constituting the core portion to be below the above upper limit, the polymerization reaction when the polymer constituting the core portion can be prepared can be carried out well.

[0074] ==(Meth)acrylate monomer unit==

[0075] The (meth)acrylate monomer unit is a repeating unit from a (meth)acrylate monomer. Here, in this specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid. Moreover, if the polymer constituting the core portion contains a (meth)acrylate monomer unit, it is possible to impart appropriate electrolyte affinity to the obtained electrode composite material layer, and the rate characteristics of the electrochemical element having such an electrode composite material layer can be further improved.

[0076] Examples of the (meth)acrylic acid ester monomer include alkyl (meth)acrylate monomers having 1 ethylenically unsaturated bond. Examples of the alkyl (meth)acrylate monomer include alkyl (meth)acrylate monomers having a linear alkyl group and alkyl (meth)acrylate monomers having a branched alkyl group. For example, as (meth) acrylate monomers, there can be mentioned: methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, amyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, alkyl acrylates such as stearyl acrylate; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, amyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, alkyl methacrylates such as stearyl methacrylate, etc. Among them, from the viewpoint of further improving the rate characteristics of the electrochemical element, butyl acrylate and methyl methacrylate are more preferably used. In addition, they can use only one kind, and two or more kinds can also be used in combination.

[0077] Moreover, all repeating units contained in the polymer constituting the core portion are set to 100.00 mass %, and the content ratio of the (methyl) acrylate monomer unit in the polymer constituting the core portion is preferably 30.00 mass % or more, more preferably 40.50 mass % or more, preferably 98.00 mass % or less, more preferably 95.60 mass % or less. By making the content ratio of the (methyl) acrylate monomer unit in the polymer constituting the core portion within the above range, it is possible to give the obtained electrode composite material layer suitable electrolyte affinity, and it is possible to further improve the rate characteristics of the electrochemical element with this electrode composite material layer.

[0078] ==Other monomer units==

[0079] Furthermore, the polymer constituting the core portion may also contain other monomer units from other monomers that can be copolymerized with the above-mentioned various monomers. As other monomers that can form such other monomer units, known monomers that can be used in the manufacture of adhesive components in the electrochemical element electrode binder composition can be used. More specifically, for example, as other monomers, aromatic vinyl monomers such as styrene, α-methylstyrene, butoxystyrene, and vinylnaphthalene can be cited; cyano-containing monomers such as acrylonitrile, methacrylonitrile, 2-cyanoethyl acrylate, and 2-cyanoethyl methacrylate; amide-containing monomers such as acrylamide, dimethylacrylamide, and hydroxyethylacrylamide, etc. They can be used alone or in combination of two or more.

[0080] Furthermore, when all repeating units in the polymer constituting the core portion are taken as 100.00 mass %, the content ratio of other monomer units in the polymer constituting the core portion is preferably 50.00 mass % or less, and may be 0.00 mass %.

[0081] =Glass transition temperature=

[0082] The glass transition temperature of the polymer constituting the core portion is preferably above -40°C, more preferably above -15°C, preferably below 80°C, more preferably below 35°C, and further preferably below 26°C. If the glass transition temperature of the polymer constituting the core portion is above the above lower limit, the electrolyte swelling degree of the particulate polymer A can be reduced. Therefore, the reduction of the void portion of the electrode composite material layer caused by the excessive swelling of the particulate polymer A in the electrolyte is suppressed, and the internal resistance of the electrochemical element is reduced, thereby improving the rate characteristics of the electrochemical element. In addition, if the glass transition temperature of the polymer constituting the core portion is below the above upper limit, the compressibility of the obtained electrode composite material layer can be good, and the electrode composite material layer can be effectively densified by pressing. In addition, the glass transition temperature of the polymer constituting the core portion is usually higher than the glass transition temperature of the polymer constituting the shell portion described below. In addition, the glass transition temperature of the polymer constituting the core portion can be controlled by, for example, changing the type and / or addition amount of the (meth) acrylate monomer, changing the type or ratio of other monomers, etc. in the monomer composition for preparing the polymer constituting the core portion.

[0083] - Shell -

[0084] =Glass transition temperature=

[0085] The polymer constituting the shell portion is usually a polymer different from the polymer constituting the above-mentioned core portion. Moreover, the glass transition temperature of the polymer constituting the shell portion needs to be above -50°C, preferably above -40°C, more preferably above -35°C, and needs to be below 20°C, preferably below 10°C, more preferably below 4°C, and further preferably below -10°C. If the glass transition temperature of the polymer constituting the shell portion is above the above lower limit, the electrolyte swelling degree of the particulate polymer A can be reduced. Therefore, the void portion of the electrode composite material layer caused by excessive swelling of the particulate polymer A in the electrolyte is suppressed, and the internal resistance of the electrochemical element is reduced, thereby improving the rate characteristics of the electrochemical element. In addition, if the glass transition temperature of the polymer constituting the shell portion is below the above upper limit, the peel strength and de-powdering resistance of the obtained electrode composite material layer can be improved.

[0086] The glass transition temperature of the polymer constituting the shell portion can be controlled, for example, by changing the type and / or addition amount of the (meth)acrylate monomer or the type and / or ratio of other monomers in the monomer composition used for preparing the polymer constituting the shell portion described below.

[0087] =Composition=

[0088] The polymer constituting the shell portion is not particularly limited, and may include, for example, a (meth)acrylic acid ester monomer unit, an acid group-containing monomer unit, a hydroxyl group-containing monomer unit, a crosslinking monomer unit, and the like.

[0089] ==(Meth)acrylate monomer unit==

[0090] The (meth)acrylate monomer unit is a repeating unit derived from a (meth)acrylate monomer. If the polymer constituting the shell portion includes the (meth)acrylate monomer unit, the peel strength and the powder removal resistance of the obtained electrode composite material layer can be further improved.

[0091] As the (meth)acrylate monomer, the above-mentioned (meth)acrylate monomer in the "granular polymer A" can be used. In addition, from the viewpoint of further improving the peel strength and powder removal resistance of the electrode composite material layer, butyl acrylate and methyl methacrylate are preferably used as the (meth)acrylate monomer.

[0092] In addition, all repeating units contained in the polymer constituting the shell portion are set to 100.00% by mass, and the content ratio of the (methyl) acrylate monomer unit in the polymer constituting the shell portion is preferably 40.00% by mass or more, more preferably 78.00% by mass or more, more preferably 92.00% by mass or more, preferably 99.00% by mass or less, more preferably 98.00% by mass or less, and more preferably 95.00% by mass or less. By making the content ratio of the (methyl) acrylate monomer unit in the polymer constituting the shell portion within the above range, the peel strength and the resistance to de-powdering of the obtained electrode composite material layer can be further improved.

[0093] ==Acid group-containing monomer unit==

[0094] The acid group-containing monomer unit is a repeating unit derived from an acid group-containing monomer. If the polymer constituting the shell portion contains the acid group-containing monomer unit, the peel strength and the powder removal resistance of the obtained electrode composite material layer can be further improved.

[0095] As the acid group-containing monomer, the acid group-containing monomer described above in the section of "Particulate polymer A" can be used. In order to further improve the peel strength and powder removal resistance of the electrode composite material layer, acrylic acid is preferably used as the acid group-containing monomer.

[0096] In addition, all repeating units contained in the polymer constituting the shell portion are set to 100.00% by mass, and the proportion of the acid-containing monomeric unit in the polymer constituting the shell portion is preferably 0.50% by mass or more, more preferably 1.00% by mass or more, further preferably 1.50% by mass or more, particularly preferably 2.60% by mass or more, preferably 10.00% by mass or less, more preferably 7.00% by mass or less, and further preferably 5.00% by mass or less. By making the proportion of the acid-containing monomeric unit in the polymer constituting the shell portion within the above range, the peel strength and the resistance to powdering of the obtained electrode composite material layer can be further improved.

[0097] ==Hydroxyl-containing monomer unit==

[0098] The hydroxyl-containing monomer unit is a repeating unit derived from a hydroxyl-containing monomer. Furthermore, if the polymer constituting the shell portion contains a hydroxyl-containing monomer unit, the peel strength and the powder removal resistance of the obtained electrode composite material layer can be further improved.

[0099] Examples of the hydroxyl-containing monomeric unit include 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, etc. In addition, 2-hydroxyethyl acrylate is preferably used from the viewpoint of further improving the peel strength and resistance to powdering of the electrode composite material layer.

[0100] The content ratio of the hydroxyl group-containing monomer unit in the polymer constituting the shell portion can be arbitrarily adjusted within a range in which the desired effects of the present invention can be obtained.

[0101] ==Crosslinking monomer unit==

[0102] The crosslinkable monomer unit is a repeating unit from a crosslinkable monomer. Furthermore, if the polymer constituting the shell portion contains a crosslinkable monomer unit, the electrolyte swelling degree of the granular polymer A can be reduced. Therefore, the reduction of the void portion of the electrode composite material layer caused by excessive swelling of the granular polymer A in the electrolyte can be suppressed, and the internal resistance of the electrochemical element can be reduced, thereby further improving the rate characteristics of the electrochemical element. In addition, as a crosslinkable monomer, the above-mentioned crosslinkable monomer in the "core portion" item can be used.

[0103] Moreover, all repeating units contained in the polymer constituting the shell portion are set to 100.00% by mass, and the content ratio of the crosslinkable monomer unit in the polymer constituting the shell portion is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, further preferably 0.40% by mass or more, preferably 4.00% by mass or less, and more preferably 1.00% by mass or less. By making the content ratio of the crosslinkable monomer unit in the polymer constituting the shell portion to be above the above lower limit, the electrolyte swelling degree of the binding material can be further reduced, so the internal resistance of the electrochemical element with the obtained electrode composite material layer can be further reduced, and the rate characteristics of this electrochemical element can be further improved. In addition, by making the content ratio of the crosslinkable monomer unit in the polymer constituting the shell portion to be below the above upper limit, the polymerization reaction when preparing the polymer constituting the core portion can be carried out well.

[0104] -Mass ratio of core to shell-

[0105] The mass ratio of the core portion and the shell portion of the granular polymer A is not particularly limited, and the granular polymer A is set to 100 mass % as a whole, and the mass ratio of the shell portion in the granular polymer A is preferably 10 mass % or more, more preferably 15 mass % or more, more preferably 20 mass % or more, preferably 30 mass % or less, and more preferably 25 mass % or less. If the mass ratio of the shell portion in the granular polymer A is above the above lower limit, the peel strength and the resistance to de-powdering of the obtained electrode composite material layer can be further improved. On the other hand, if the mass ratio of the shell portion is below the above upper limit, the electrolyte swelling degree of the granular polymer A can be reduced, and the rate characteristics of the electrochemical element with the obtained electrode composite material layer can be further improved.

[0106] [Viscosity of granular polymer A]

[0107] The particulate polymer A was mixed with an organic solvent at a concentration of 8 mass % and the mixed solution was subjected to a shear rate of 1 s -1 The viscosity of the mixture is preferably 1000 mPa·s or less, more preferably 500 mPa·s or less, and further preferably 150 mPa·s or less. In addition, the organic solvent is an organic solvent contained in both the granular polymer A and the polymer B in the binder composition. Such an organic solvent will be described later. If the mixed liquid of the granular polymer A and the organic solvent is subjected to a shearing speed of 1s -1 When the viscosity is 1000 mPa·s or less, the electrode active material can be added to the slurry composition containing the binder composition at a sufficient solid content concentration, so that the electrochemical device having the electrode composite material layer formed using the slurry composition can exhibit more excellent rate characteristics.

[0108] [Amount of organic solvent-insoluble components in granular polymer A]

[0109] The amount of insoluble components when the granular polymer A is mixed with an organic solvent at a concentration of 8% by mass is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 94% by mass or more, and can also be 100% by mass, that is, insoluble in an organic solvent. In addition, the organic solvent is an organic solvent contained in both the granular polymer A and the polymer B in the binder composition. This organic solvent will be described later. If the amount of organic solvent insoluble components of the granular polymer A is above the above lower limit, the battery characteristics of the secondary battery having the obtained electrode composite material layer can be improved. In addition, the amount of organic solvent insoluble components can be controlled by adjusting the amount of crosslinking monomer added in the monomer composition for preparing the granular polymer A. In addition, the above-mentioned insoluble components can be measured by the method described in the embodiments of this specification.

[0110] [Method for preparing granular polymer A]

[0111] The granular polymer A having the core-shell structure can be prepared, for example, by using monomers for forming a core portion polymer and monomers for forming a shell portion polymer, and polymerizing them stepwise while changing the ratio of these monomers over time. Specifically, the granular polymer A can be prepared by a continuous multi-stage emulsion polymerization method and a multi-stage suspension polymerization method in which a polymer in a later stage is successively covered with a polymer in an earlier stage.

[0112] Therefore, an example of the case where the particulate polymer A having the above core-shell structure is obtained by a multi-stage emulsion polymerization method is shown below.

[0113] When performing polymerization, according to conventional methods, as emulsifiers, anionic surfactants such as sodium polyoxyethylene alkyl ether sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, etc.; nonionic surfactants such as polyoxyethylene nonylphenyl ether, sorbitan monolaurate, etc.; or cationic surfactants such as octadecylamine acetate, etc. can be used. In addition, as polymerization initiators, peroxides such as tert-butyl peroxy-2-ethylhexanoate, potassium persulfate, ammonium persulfate, cumene peroxide, etc.; azo compounds such as 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)-propionamide) and 2,2'-azobis(2-amidinopropane) hydrochloride can be used.

[0114] Moreover, as the polymerization sequence, the monomers forming the core portion are first mixed with an emulsifier, and the granular polymer constituting the core portion is obtained by emulsion polymerization. Furthermore, the monomers forming the shell portion are polymerized in the presence of the granular polymer constituting the core portion, thereby obtaining the granular polymer A having the core-shell structure.

[0115] At this time, from the viewpoint of making the shell part partially cover the outer surface of the core part, the monomers of the polymer forming the shell part are preferably supplied to the polymerization system in batches or continuously. By supplying the monomers of the polymer forming the shell part to the polymerization system in batches or continuously, the polymer constituting the shell part is formed into particles, and the particles are bonded to the core part, thereby forming a shell part that partially covers the core part.

[0116] [Content ratio of granular polymer A]

[0117] The content ratio of the granular polymer A in the binding material is preferably more than 5% by mass, more preferably more than 10% by mass, more preferably more than 20% by mass, preferably less than 40% by mass, more preferably less than 35% by mass. If the content ratio of the granular polymer A in the binding material is more than the above lower limit, the peel strength and the resistance to de-powdering of the obtained electrode composite material layer can be further improved. On the other hand, if the content ratio of the granular polymer A in the binding material is below the above upper limit, the coating property of the slurry composition can be fully and highly ensured.

[0118] <<Polymer B>>

[0119] Polymer B is a component that can impart appropriate viscosity to the slurry composition comprising the binder composition. Thus, the coating property of the slurry composition can be improved, and the obtained electrode composite material layer can be imparted with excellent peel strength and resistance to powdering. Furthermore, the electrode active material etc. can be added without sedimentation in the slurry composition at a sufficient solid content concentration, so that the electrochemical element having the obtained electrode composite material layer can be imparted with high rate characteristics.

[0120] [Viscosity]

[0121] The polymer B was mixed with an organic solvent at a concentration of 8 mass % to obtain a mixed solution at a shear rate of 1 s -1 The viscosity at 100 mPa·s or more is required, preferably 300 mPa·s or more, more preferably 1000 mPa·s or more, and further preferably 4720 mPa·s or more. It is required to be 10000 mPa·s or less, preferably 9000 mPa·s or less, more preferably 8000 mPa·s or less, and further preferably 5300 mPa·s or less. In addition, the organic solvent is an organic solvent contained in both the granular polymer A and the polymer B in the binder composition. This organic solvent will be described later. If the mixed solution of polymer B and the organic solvent is subjected to a shearing speed of 1 s -1 When the viscosity is 100 mPa·s or more, the slurry composition containing the binder composition has excellent coating properties, so the obtained electrode composite material layer can exhibit excellent peel strength and resistance to powder removal. On the other hand, if the mixed solution of polymer B and organic solvent is subjected to a shear rate of 1s -1 When the viscosity is 10000 mPa·s or less, the electrode active material can be added to the slurry composition containing the binder composition at a sufficient solid content concentration, so that the electrochemical device having the electrode composite material layer formed using the slurry composition can exhibit excellent rate characteristics.

[0122] [structure]

[0123] As long as polymer B has the above-mentioned prescribed properties, it is not particularly limited and can be granular or non-granular in an organic solvent, usually non-granular. In addition, the organic solvent is an organic solvent that the granular polymer A and polymer B contain simultaneously in the binder composition. This organic solvent is described later.

[0124] [composition]

[0125] The polymer B is not particularly limited, and may include, for example, a cyano group-containing monomer unit, a (meth)acrylate monomer unit, an acid group-containing monomer unit, an amide group-containing monomer unit, and the like.

[0126] -Cyanide-containing monomer units-

[0127] The cyano-containing monomer unit is a repeating unit from a cyano-containing monomer. Moreover, if polymer B includes a cyano-containing monomer unit, the electrolyte swelling degree of polymer B can be reduced. Therefore, the void portion of the electrode composite material layer caused by excessive swelling of polymer B in the electrolyte is suppressed to reduce, and the internal resistance of the electrochemical element is reduced, thereby further improving the rate characteristics of the electrochemical element. In addition, if polymer B includes a cyano-containing monomer unit, since the polymer strength of polymer B is improved, the peel strength and the resistance to powdering of the obtained electrode composite material layer can be further improved.

[0128] As the cyano group-containing monomer, the cyano group-containing monomer described above in the section "Particulate polymer A" can be used. In addition, from the viewpoint of further improving the peel strength and powder removal resistance of the electrode composite material layer and the rate characteristics of the electrochemical element, acrylonitrile is preferably used as the cyano group-containing monomer.

[0129] All repeating units contained in polymer B are set to 100.0% by mass, and the content ratio of the cyano-containing monomer unit in polymer B is preferably 60.0% by mass or more, more preferably 65.0% by mass or more, more preferably 80.0% by mass or more, more preferably 90.0% by mass or more, preferably 99.0% by mass or less, more preferably 95.0% by mass or less, and more preferably 93.0% by mass or less. If the content ratio of the cyano-containing monomer unit in polymer B is above the above lower limit, the peel strength and resistance to de-powdering of the obtained electrode composite material layer can be further improved, and the rate characteristics of the electrochemical element with such an electrode composite material layer can be further improved. On the other hand, if the content ratio of the cyano-containing monomer unit in polymer B is below the above upper limit, the compressibility of the obtained electrode composite material layer can be made good, and the electrode composite material layer can be effectively densified by pressing.

[0130] -(Meth)acrylate monomer unit-

[0131] The (meth)acrylate monomer unit is a repeating unit derived from a (meth)acrylate monomer. If the polymer B contains the (meth)acrylate monomer unit, the compressibility of the obtained electrode composite material layer can be improved, and the electrode composite material layer can be efficiently densified by pressing.

[0132] As the (meth)acrylate monomer, the (meth)acrylate monomer described above in the section of "Particulate Polymer A" can be used. In addition, from the viewpoint of improving the compressibility of the electrode composite material layer, butyl acrylate is preferably used as the (meth)acrylate monomer.

[0133] All repeating units contained in polymer B are set to 100% by mass, and the content ratio of the (meth) acrylate monomer unit in polymer B is preferably 1.5% by mass or more, more preferably 2.0% by mass or more, more preferably 2.5% by mass or more, more preferably 4.0% by mass or more, preferably 60.0% by mass or less, more preferably 40.0% by mass or less, more preferably 32.0% by mass or less, and more preferably 10.0% by mass or less. If the content ratio of the (meth) acrylate monomer unit in polymer B is within the above range, the compressibility of the obtained electrode composite material layer can be further improved, and the electrode composite material layer can be further densified by pressing.

[0134] -Acid group-containing monomer unit-

[0135] The acid group-containing monomer unit is a repeating unit derived from an acid group-containing monomer. If the polymer B contains the acid group-containing monomer unit, the peel strength and the powder removal resistance of the obtained electrode composite material layer can be further improved.

[0136] As the acid group-containing monomer, the acid group-containing monomer described above in the section of “Particulate polymer A” can be used. In order to further improve the peel strength and powder removal resistance of the electrode composite material layer, acrylic acid is preferably used as the acid group-containing monomer.

[0137] The total repeating units contained in polymer B are set to 100% by mass, and the content ratio of the acid-containing monomer unit in polymer B is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, further preferably 1.5% by mass or more, further preferably 2.0% by mass or more, preferably 40.0% by mass or less, more preferably 20.0% by mass or less, and further preferably 5.0% by mass or less. If the content ratio of the acid-containing monomer unit in polymer B is within the above range, the peel strength and the resistance to powdering of the obtained electrode composite material layer can be further improved.

[0138] -Amide-containing monomer units-

[0139] The amide group-containing monomer unit is a repeating unit derived from an amide group-containing monomer. As the amide group-containing monomer, the amide group-containing monomer described above in the section "Particulate polymer A" can be used. Among them, acrylamide is preferably used as the amide group-containing monomer.

[0140] The content ratio of the amide group-containing monomer unit in the polymer B can be arbitrarily adjusted within a range in which the desired effects of the present invention can be obtained.

[0141] [Amount of organic solvent-insoluble components of polymer B]

[0142] The amount of insoluble components when polymer B is mixed with an organic solvent at a concentration of 8% by mass is preferably 50% by mass or less, more preferably 30% by mass or less, and further preferably 10% by mass or less. In addition, the amount of insoluble components when polymer B is mixed with an organic solvent can be more than 0.1% by mass. In addition, the organic solvent is an organic solvent that particulate polymer A and polymer B contain simultaneously in the binder composition. This organic solvent is described later. If the amount of organic solvent insoluble components of polymer B is below the above-mentioned upper limit, the solid content concentration of the slurry composition prepared using the binder composition can be further improved. It is speculated that this is because polymer B in the binder composition plays a role in a way that solid components such as electrode active materials are suppressed from agglomerating with each other. In addition, the above-mentioned insoluble amount can be measured by the method described in the embodiments of this specification.

[0143] [Method for preparing polymer B]

[0144] The method for preparing the polymer B is not particularly limited. The polymer B can be prepared, for example, by adding a polymerization initiator such as potassium persulfate to allow a monomer composition containing the above monomers to undergo a polymerization reaction.

[0145] Here, the content ratio of each monomer in the monomer composition used for preparing the polymer B can be determined based on the content ratio of each repeating unit in the polymer B.

[0146] The polymerization method is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. can be used. In addition, any reaction such as ion polymerization, radical polymerization, living radical polymerization, etc. can be used as the polymerization reaction.

[0147] [Content ratio of polymer B]

[0148] The content ratio of polymer B in the binding material is preferably 60% by mass or more, more preferably 65% ​​by mass or more, preferably 95% by mass or less, more preferably 90% by mass or less, and more preferably 80% by mass or less. If the content ratio of polymer B in the binding material is above the above lower limit, the peel strength and the resistance to de-powdering of the obtained electrode composite material layer can be further improved, and the rate characteristics of the electrochemical element with such an electrode composite material layer can be further improved. On the other hand, if the content ratio of polymer B in the binding material is below the above upper limit, the peel strength and the resistance to de-powdering of the obtained electrode composite material layer can be further improved.

[0149] <<Viscosity of the bonding material (granular polymer A and polymer B)>>

[0150] The binder (particulate polymer A and polymer B) was mixed with an organic solvent at a concentration of 8 mass % and the resulting mixture was subjected to a shearing rate of 1 s -1 The viscosity at 100 mPa·s or more is preferably 300 mPa·s or more, further preferably 1000 mPa·s or more, further preferably 5000 mPa·s or more, preferably 10000 mPa·s or less, more preferably 9000 mPa·s or less, further preferably 8000 mPa·s or less. In addition, the organic solvent is an organic solvent contained in both the granular polymer A and the polymer B in the adhesive composition. This organic solvent will be described later. If the mixed liquid of the adhesive material and the organic solvent is subjected to a shearing speed of 1s -1 When the viscosity is 100 mPa·s or more, the slurry composition containing the binder composition has excellent coating properties, so the obtained electrode composite material layer can exhibit better peel strength and resistance to powder removal. On the other hand, if the mixed solution of the binder and the organic solvent is subjected to a shear rate of 1s -1 When the viscosity is 10000 mPa·s or less, the electrode active material can be added to the slurry composition containing the binder composition at a sufficient solid content concentration, so that the electrochemical device having the electrode composite material layer formed using the slurry composition can exhibit more excellent rate characteristics.

[0151] Furthermore, the mixed solution obtained by mixing the binder with an organic solvent at a concentration of 8 mass % was subjected to a shearing speed of 1 s -1 The viscosity is preferably above 5000 mPa. If the mixed solution of the adhesive material and the organic solvent is subjected to a shearing speed of 1 s -1 When the viscosity is 5000 mPa or more, the peel strength and the resistance to powder falling of the obtained electrode composite material layer can be further improved, and the electrochemical element having the electrode composite material layer can exhibit more excellent rate characteristics.

[0152] <Organic Solvents>

[0153] In addition, examples of organic solvents for the adhesive composition of the present invention include alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, and amyl alcohol; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; ether, diethyl ether, and diethyl ether; Ethers such as alkanes and tetrahydrofuran; amide-based polar organic solvents such as N,N-dimethylformamide and N-methyl-2-pyrrolidone (NMP); aromatic hydrocarbons such as toluene, xylene, chlorobenzene, o-dichlorobenzene, and p-dichlorobenzene. They can be used alone or in combination of two or more. In addition, from the perspective of further improving the peel strength and powder removal resistance of the electrode composite material layer and the rate characteristics of the electrochemical element, NMP is preferably used as the organic solvent.

[0154] <Other ingredients>

[0155] The binder composition of the present invention may also contain components such as reinforcing materials, leveling agents, viscosity modifiers, electrolyte additives, etc. in addition to the above components. These components can use known components, such as the components described in International Publication No. 2012 / 115096. In addition, these components can be used alone or in combination of two or more in any ratio.

[0156] <Preparation of Adhesive Composition>

[0157] Furthermore, the binder composition of the present invention can be prepared by mixing the above-mentioned granular polymer A, polymer B, organic solvent and any other components using a known method. Specifically, the binder composition can be prepared by mixing the above-mentioned components using a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, a chopper, an ultrasonic disperser, a homogenizer, a planetary mixer, or Filmix.

[0158] When the particulate polymer A and the polymer B are polymerized separately in an organic solvent, a dispersion in which the particulate polymer A is dispersed in an organic solvent and a dispersion in which the polymer B is dissolved or dispersed in an organic solvent can be directly mixed to prepare the binder composition.

[0159] (Slurry composition for electrochemical device electrodes)

[0160] The slurry composition for the electrochemical element electrode of the present invention comprises an electrode active material and the above-mentioned binder composition, and optionally further comprises a conductive material and other components. That is, the slurry composition of the present invention generally contains an electrode active material, the above-mentioned particulate polymer A and polymer B in the above-mentioned organic solvent, and optionally further comprises a conductive material and / or other components. Moreover, the slurry composition of the present invention comprises the above-mentioned binder composition, so that the electrode composite material layer formed using the slurry composition of the present invention can have excellent peel strength and resistance to powdering even when it is made into a high density and high surface density, and can enable the electrochemical element to exert excellent rate characteristics.

[0161] In addition, the following describes the case where the slurry composition for an electrode of an electrochemical element, which is an example, is a slurry composition for an electrode of a lithium-ion secondary battery. However, the present invention is not limited to the following single example.

[0162] <Electrode active material>

[0163] The electrode active material is a substance that transfers electrons in the electrode of a secondary battery. Moreover, as the positive electrode active material for a lithium-ion secondary battery, a substance that can absorb and release lithium is generally used.

[0164] Specifically, as the positive electrode active material for a lithium-ion secondary battery, there is no particular limitation, and examples include lithium-containing cobalt oxide (LiCoO2), lithium manganate (LiMn2O4), lithium-containing nickel oxide (LiNiO2), lithium-containing composite oxide of Co-Ni-Mn (Li(CoMnNi)O2), lithium-containing composite oxide of Ni-Mn-Al, lithium-containing composite oxide of Ni-Co-Al, olivine-type lithium iron phosphate (LiFePO4), olivine-type lithium manganese phosphate (LiMnPO4), Li2MnO3-LiNiO2-based solid solution, and lithium-excess spinel compounds represented by Li 1+x Mn 2-x O4 (0 < X < 2), Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 O2, LiNi 0.5 Mn 1.5 O4 and other known positive electrode active materials.

[0165] In addition, the addition amount and particle size of the positive electrode active material are not particularly limited and can be the same as those of the positive electrode active material used in the past.

[0166] Furthermore, as the negative electrode active material for a lithium-ion secondary battery, examples include carbon-based negative electrode active materials, metal-based negative electrode active materials, and negative electrode active materials obtained by combining them.

[0167] Here, the carbon-based negative electrode active material refers to an active material having a carbon main skeleton that can intercalate lithium (also referred to as "doping"). Examples of the carbon-based negative electrode active material include carbonaceous materials and graphitic materials.

[0168] Moreover, as the carbonaceous material, examples include easily graphitizable carbon, and hardly graphitizable carbon having a structure close to an amorphous structure typified by vitreous carbon.

[0169] Here, examples of graphitizable carbon include carbon materials made from tar pitch obtained from petroleum or coal, and specific examples include coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fibers, and pyrolysis vapor-grown carbon fibers.

[0170] Examples of the hardly graphitizable carbon include phenolic resin sintered bodies, polyacrylonitrile-based carbon fibers, quasi-isotropic carbon, furfuryl alcohol resin sintered bodies (PFA), and hard carbon.

[0171] Furthermore, examples of the graphite material include natural graphite and artificial graphite.

[0172] Here, examples of artificial graphite include artificial graphite obtained by heat treating carbon including easily graphitized carbon at 2800°C or above, graphitized MCMB obtained by heat treating MCMB at 2000°C or above, and graphitized mesophase pitch-based carbon fibers obtained by heat treating mesophase pitch-based carbon fibers at 2000°C or above.

[0173] In addition, the metal-based negative electrode active material is an active material containing a metal, generally referring to an active material containing an element capable of inserting lithium in the structure, and having a theoretical capacity of 500 mAh / g or more per unit mass in the case of inserting lithium. As a metal-based active material, for example, lithium metal, a single metal that can form a lithium alloy (for example, Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.) and its alloy, and their oxides, sulfides, nitrides, silicides, carbides, phosphides, etc. can be used. Among them, as a metal-based negative electrode active material, an active material (silicon-based negative electrode active material) containing silicon is preferably used. This is because by using a silicon-based negative electrode active material, the lithium-ion secondary battery can be made high-capacity.

[0174] Examples of the silicon-based negative electrode active material include silicon (Si), alloys containing silicon, SiO, SiO x , a composite of a Si-containing material and conductive carbon in which a Si-containing material is coated with conductive carbon or composited, etc. In addition, these silicon-based negative electrode active materials may be used alone or in combination of two or more.

[0175] The amount and particle size of the negative electrode active material added are not particularly limited and may be the same as those of conventionally used negative electrode active materials.

[0176] <Conductive Materials>

[0177] The conductive material is a material for ensuring electrical contact between electrode active materials. In addition, as the conductive material, carbon black (e.g., acetylene black, Ketjen black (registered trademark), furnace black, etc.), single-layer or multi-layer carbon nanotubes (multi-layer carbon nanotubes include stacked cups), carbon nanohorns, vapor-grown carbon fibers, milled carbon fibers obtained by sintering and crushing polymer fibers, single-layer or multi-layer graphene, carbon non-woven fabric sheets obtained by sintering non-woven fabrics formed from polymer fibers, and other conductive carbon materials can be used; fibers or foils of various metals, etc.

[0178] These can be used alone or in combination of two or more. In addition, the amount and particle size of the conductive material added are not particularly limited and can be the same as those of the conductive material conventionally used.

[0179] <Binder Composition>

[0180] As the binder composition, a binder composition for electrochemical element electrodes containing the above-mentioned particulate polymer A, polymer B and an organic solvent is used.

[0181] Here, the total addition amount of particulate polymer A, polymer B, electrode active material and (in the case of containing) conductive material is set to 100 mass %, and the content ratio of the binding material (particulate polymer A and polymer B) in the solid component of the slurry composition is preferably 0.3 mass % or more, preferably 3 mass % or less, and more preferably 2.5 mass % or less. If the content ratio of the binding material in the solid component of the slurry composition is within the above range, the peel strength and the resistance to powdering of the obtained electrode composite material layer can be further improved.

[0182] <Other ingredients>

[0183] The other components that can be added to the slurry composition are not particularly limited, and examples thereof include the same other components that can be added to the binder composition of the present invention. In addition, the other components may be used alone or in combination of two or more in any ratio.

[0184] <Preparation of slurry composition>

[0185] The above-mentioned slurry composition can be prepared by dissolving or dispersing the above-mentioned components in an organic solvent. Specifically, the above-mentioned components can be mixed with an organic solvent using a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, a shredder, an ultrasonic disperser, a homogenizer, a planetary mixer, and Filmix, thereby preparing the slurry composition. In addition, as an organic solvent that can be used in the preparation of the slurry composition, the above-mentioned organic solvent in the item "binder composition for electrochemical element electrodes" can be cited. In addition, as an organic solvent that can be used in the preparation of the slurry composition, an organic solvent contained in the binder composition can be used.

[0186] In addition, for example, after mixing the particulate polymer A, the polymer B and the organic solvent, the preparation of the binder composition to which the electrode active material and other optional components are added and the preparation of the slurry composition described below may be carried out simultaneously.

[0187] (Electrode for electrochemical device)

[0188] The electrode for electrochemical element of the present invention is characterized in that it has an electrode composite material layer formed using the slurry composition of the present invention. More specifically, the electrode of the present invention has a current collector, an electrode composite material layer formed on the current collector, and the electrode composite material layer is formed using the slurry composition of the present invention. That is, the electrode composite material layer of the electrode of the present invention contains at least an electrode active material, a particulate polymer A, and a polymer B, and optionally contains other components. In addition, the components contained in the electrode composite material layer are those contained in the above-mentioned slurry composition, and the preferred existence ratio of these components is the same as the preferred existence ratio of each component in the slurry composition.

[0189] Moreover, since the electrode composite material layer of the electrode of the present invention is formed using the slurry composition of the present invention, even when it is made into high density and high surface density, it can have excellent peel strength and resistance to powder removal, and can provide high rate characteristics to the electrochemical element.

[0190] <Manufacturing method>

[0191] The electrode of the present invention is produced through, for example, a step of applying the slurry composition on a current collector (coating step) and a step of drying the slurry composition applied on the current collector to form an electrode composite material layer on the current collector (drying step).

[0192] <<Coating process>>

[0193] There is no particular limitation on the method of applying the slurry composition to the current collector, and a known method can be used. Specifically, as the coating method, a doctor blade method, a dipping method, a reverse roll coating method, a direct roll coating method, a gravure method, an extrusion method, a brush coating method, etc. can be used. At this time, the slurry composition can be applied only on one side of the current collector, or it can be applied on both sides.

[0194] The thickness of the slurry film on the current collector after application and before drying can be appropriately set according to the density and thickness of the electrode composite material layer obtained by drying.

[0195] Here, as the current collector for coating the slurry composition, a material having conductivity and electrochemical durability can be used. Specifically, as the current collector, for example, a current collector formed of iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. In addition, the above materials can be used alone or in combination of two or more in any ratio.

[0196] <<Drying process>>

[0197] The method for drying the slurry composition on the current collector is not particularly limited, and a known method can be used, for example: a drying method using warm air, hot air, or low-humidity air; a vacuum drying method; a drying method using infrared rays, electron beams, etc. By drying the slurry composition on the current collector in this way, an electrode composite material layer can be formed on the current collector, and an electrode for an electrochemical element having a current collector and an electrode composite material layer can be obtained.

[0198] In addition, after the drying process, die pressing or roll pressing etc. can be used to apply pressure treatment to the electrode composite material layer. By applying pressure treatment, the adhesion strength of the components in the electrode composite material layer and the adhesion strength of the electrode composite material layer and the current collector (peel strength of the electrode composite material layer) can be improved. In addition, in the case where the electrode composite material layer includes a curable polymer, it is preferred that the above-mentioned polymer is cured after the electrode composite material layer is formed.

[0199] (Electrochemical Components)

[0200] The electrochemical element of the present invention is not particularly limited, and is, for example, a lithium ion secondary battery and a double electric layer capacitor, preferably a lithium ion secondary battery. In addition, the electrochemical element of the present invention is characterized in that it has the above-mentioned electrode for the electrochemical element of the present invention. Such an electrochemical element can exhibit high rate characteristics.

[0201] Here, as an example, the case where the electrochemical element is a lithium ion secondary battery is described below, but the present invention is not limited to the following example. The lithium ion secondary battery as the electrochemical element of the present invention usually has electrodes (positive and negative electrodes), an electrolyte and a separator, and at least one of the positive and negative electrodes is an electrode for the electrochemical element of the present invention. That is, the lithium ion secondary battery of the present invention usually has the above-mentioned electrode of the present invention, and may also arbitrarily have an electrode other than the electrode of the present invention. In addition, the lithium ion secondary battery of the present invention preferably has the electrode of the present invention as the positive electrode.

[0202] <Electrodes other than the electrode of the present invention>

[0203] Here, as an electrode other than the electrode of the present invention that can be used in the lithium ion secondary battery of the present invention, there is no particular limitation, and a known electrode that can be used for the manufacture of a lithium ion secondary battery can be used. Specifically, as an electrode other than the electrode of the present invention, an electrode formed by forming an electrode composite material layer on a current collector using a known manufacturing method can be used.

[0204] <Electrolyte>

[0205] As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent can generally be used. As the supporting electrolyte of a lithium ion secondary battery, for example, a lithium salt can be used. As a lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. can be cited. Among them, LiPF6, LiClO4, CF3SO3Li are preferred, and LiPF6 is particularly preferred because they are easily soluble in solvents and show a high degree of dissociation. In addition, the electrolyte can be used alone or in combination of two or more in any ratio. Generally, there is a tendency that the more a supporting electrolyte with a high degree of dissociation is used, the higher the lithium ion conductivity is, so the lithium ion conductivity can be adjusted according to the type of supporting electrolyte.

[0206] As the organic solvent used in the electrolyte, as long as it can dissolve the supporting electrolyte, it is not particularly limited, preferably using carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc. In addition, a mixed solution of these solvents can also be used. Among them, due to the high dielectric constant and wide stable potential region, carbonates are preferably used, and a mixture of ethylene carbonate and diethyl carbonate is further preferably used.

[0207] The concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. In addition, a known additive such as vinylene carbonate can be added to the electrolytic solution.

[0208] <Spacer>

[0209] There is no particular limitation on the separator, and for example, the separators described in Japanese Patent Publication No. 2012-204303 can be used. Among them, from the viewpoint of being able to thin the overall film thickness of the separator, thereby being able to increase the ratio of the electrode active material in the lithium ion secondary battery and increasing the capacity per unit volume, a microporous membrane formed of a polyolefin-based (polyethylene, polypropylene, polybutylene, polyvinyl chloride) resin is preferred.

[0210] <Method for producing lithium-ion secondary battery>

[0211] The lithium-ion secondary battery of the present invention can be manufactured by, for example, the following method: overlapping the positive electrode and the negative electrode with a separator, winding and bending them according to the battery shape as needed, placing them in a battery container, injecting electrolyte into the battery container, and sealing them. In order to prevent the internal pressure of the secondary battery from rising, overcharging and discharging, etc., overcurrent protection elements such as fuses and PTC elements; porous metal mesh; guide plates, etc. can also be provided as needed. The shape of the lithium-ion secondary battery can be, for example, any of coin-shaped, button-shaped, sheet-shaped, cylindrical, square, flat, etc.

[0212] Example

[0213] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.

[0214] In a polymer produced by copolymerizing a plurality of monomers, unless otherwise specified, the ratio of a monomer unit formed by polymerizing a certain monomer in the polymer generally corresponds to the ratio (feed ratio) of the certain monomer in all monomers used for polymerization of the polymer.

[0215] Moreover, in the embodiments and comparative examples, the mass ratio of the shell portion in the granular polymer A, the glass transition temperature of the polymers in the core and shell portions of the granular polymer A, the properties of the granular polymer A, polymer B and the binding material, the electrolyte swelling degree of the binding material, the amount of NMP insoluble components of the granular polymer A and polymer B, the peel strength and resistance to powder removal of the positive electrode composite material layer, and the rate characteristics of the lithium ion secondary battery are calculated, measured and evaluated by the following methods.

[0216] <Mass Ratio of Shell Portion in Particulate Polymer A>

[0217] The mass ratio of the shell part in the particulate polymer A is calculated by the following formula based on the total mass M1 of all monomers contained in the monomer composition for forming the core part and the total mass M2 of all monomers contained in the monomer composition for forming the shell part.

[0218] Mass ratio of shell (%) = {M2 / (M1+M2)}×100

[0219] <Glass transition temperature (Tg) of the core and shell polymers of the particulate polymer A>

[0220] An appropriate amount of N-methyl-2-pyrrolidone (NMP) as an organic solvent was added to the aqueous dispersion of the granular polymer A prepared in the examples and comparative examples to obtain a mixture. Thereafter, water and excess NMP were removed from the mixture by vacuum distillation at 90° C. to obtain an NMP dispersion of the granular polymer A (solid content concentration: 9.0%).

[0221] Then, the obtained NMP dispersion of the granular polymer A is applied to a polytetrafluoroethylene sheet, and dried for 3 to 8 hours at a temperature of 80 to 120°C to obtain a cast film. The film is cut into short strips with a thickness of 1.0 ± 0.1 mm, a length of 50 ± 2 mm, and a width of 5 ± 0.1 mm to prepare a test piece for dynamic viscoelasticity measurement. As a dynamic viscoelasticity measurement device, a viscoelasticity analyzer (DMS) "EXSTARDMS5800" (manufactured by Seiko Instruments Inc.) is used, and the storage modulus, loss modulus, and tanδ are measured under the conditions of deformation mode: stretching, frequency: 1 Hz, measurement temperature: -100°C to 180°C, and heating rate: 3°C / min. The peak temperature of tanδ obtained at this time is taken as the glass transition temperature.

[0222] Here, whether the two glass transition temperatures obtained by DMS are the glass transition temperatures of the core polymer and the shell polymer is determined as follows.

[0223] First, an ultrathin section of the film obtained above is made, and an atomic force microscope (AFM) is used to measure the surface of the ultrathin section in a tapping mode to obtain a phase mapping image. Then, by comparing the elastic modulus of the core with the elastic modulus of the shell, it is determined which of the two glass transition temperatures obtained by DMS belongs to the core or the shell. For example, the elastic modulus of the core is compared with the elastic modulus of the shell. When the elastic modulus of the shell is lower, the lower one of the two glass transition temperatures is used as the glass transition temperature of the polymer of the shell, and the higher one is used as the glass transition temperature of the polymer of the core.

[0224] <Properties of Granular Polymer A, Polymer B and Binder>

[0225] An appropriate amount of N-methyl-2-pyrrolidone (NMP) as an organic solvent was added to the aqueous dispersion of the granular polymer A and the aqueous dispersion of the polymer B prepared in the examples and comparative examples to obtain a mixture. Then, a vacuum distillation was carried out at 90°C to remove water and excess NMP from the mixture to obtain a mixed solution of the granular polymer A and the polymer B with NMP (solid content concentration: 8%) as a sample for measurement. A rotational rheometer (Anton Paar Japan KK, "MCR30") was used at a temperature of 25 degrees and a shear rate of 1s -1 The viscosity of the measurement sample is measured.

[0226] In addition, the positive electrode binder composition obtained in the examples and comparative examples (mixed solution of binder and NMP (solid content concentration: 8%)) was used as a measurement sample, and the same measurement was performed as above, and the shear rate was 1 s -1 The viscosity at .

[0227] <Binder swelling degree of electrolyte>

[0228] The positive electrode binder composition prepared in the examples and comparative examples is applied to a polytetrafluoroethylene sheet and dried for 3 to 8 hours at a temperature of 80 to 120°C to obtain a cast film with a thickness of 500 μm ± 50 μm. The cast film is cut and weighed accurately to about 1 g. The mass of the obtained membrane is set to W0. The membrane is immersed in an electrolyte (composition: a 1.0M LiPF6 solution (the solvent is a mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) = 3 / 7 (volume ratio), and 2 volume % (solvent ratio) of vinyl carbonate as an additive)) at a temperature of 60°C for 3 days to swell it. Thereafter, the membrane is fished out, the electrolyte on the surface is gently wiped off, and the mass is measured. The mass of the swollen membrane is set as W1, and the electrolyte swelling degree is calculated using the following calculation formula.

[0229] Electrolyte swelling degree (mass %) = {(W1-W0) / W0} × 100

[0230] Then, the degree of swelling of the binder of the positive electrode binder composition into the electrolyte was evaluated according to the following criteria.

[0231] A: The electrolyte swelling degree is less than 300%

[0232] B: The electrolyte swelling degree is 300% or more and less than 400%

[0233] C: The electrolyte swelling degree is 400% or more and less than 500%

[0234] D: Electrolyte swelling degree is more than 500%

[0235] <NMP-Insoluble Content of Granular Polymer A and Polymer B>

[0236] 8 g of the granular polymer A and polymer B prepared in the examples and comparative examples were added to 92 g of NMP, mixed and dissolved. The mixed solution was filtered through a metal mesh of 80 mesh, and the filtrate remaining on the metal mesh was dried and weighed. The NMP insoluble content (%) was calculated by calculating the ratio of the mass (g) of the filtrate to the 8 g of granular polymer A or polymer B added.

[0237] <Peel Strength of Positive Electrode Composite Material Layer>

[0238] The lithium ion secondary battery positive electrode made in the embodiment and the comparative example is cut into a rectangle with a length of 100mm and a width of 10mm and is made into a test piece, and a transparent tape (according to the transparent tape of JIS Z1522) is pasted on the surface of the positive electrode composite material layer face down, and the stress (in addition, the transparent tape is fixed on the test bench) when one end of the current collector is stretched at a tension rate of 100mm / minute in the vertical direction is measured. 3 measurements are carried out, and its average value is obtained and used as peel strength, and evaluated by the following benchmarks. The larger the value of peel strength, the more excellent the adhesion of the positive electrode composite material layer and the current collector is.

[0239] A: Peel strength is 30N / m or more

[0240] B: Peel strength is 25 N / m or more and less than 30 N / m

[0241] C: Peel strength is 20 N / m or more and less than 25 N / m

[0242] D: Peel strength less than 20N / m

[0243] <Powder removal resistance of positive electrode composite material layer>

[0244] The positive electrode for lithium ion secondary battery produced in each example and comparative example was cut into a rectangular test piece with a length of 600 mm and a width of 500 mm, and five of the test pieces were prepared as samples. The following operations and measurements were performed on the test piece of each sample.

[0245] First, measure the initial electrode weight (P0) of a test piece of one sample. Next, use a cutter to cut 11 cuts with a width of 1 mm on the test piece, and gently wipe off the powder produced during cutting. Then, measure the electrode weight after cutting (P1). Calculate the amount of electrode powder loss using the following calculation formula.

[0246] Electrode powder removal (mass %) = {(P0-P1) / P0}×100

[0247] The above operation and measurement were repeated 5 times to obtain the average value of the powder removal amount of the electrodes of the 5 samples. Then, the powder removal resistance of the electrode composite material layer was evaluated by the following benchmark. The less the powder removal amount of the electrode, the more excellent the powder removal resistance of the electrode composite material layer.

[0248] A: The average amount of electrode powder loss is less than 0.4%

[0249] B: The average amount of electrode powder loss is 0.4% or more and less than 0.6%

[0250] C: The average amount of electrode powder loss is 0.6% or more and less than 0.8%

[0251] D: The average amount of electrode powder loss is 0.8% or more

[0252] <Rate Characteristics of Lithium Ion Secondary Batteries>

[0253] After injecting the electrolyte into the lithium ion secondary battery prepared in the embodiment and the comparative example, it was left to stand at a temperature of 25°C for 5 hours. Next, it was charged at a temperature of 25°C with a constant current method of 0.2C until the battery voltage reached 3.65V, and then aged at a temperature of 60°C for 12 hours. Then, it was discharged at a temperature of 25°C with a constant current method of 0.2C until the battery voltage reached 3.00V. Thereafter, CC-CV charging was performed at a constant current of 0.2C (the upper limit battery voltage was 4.20V), and CC discharge was performed at a constant current of 0.2C until the battery voltage reached 3.00V. This 0.2C charge and discharge was repeated 3 times.

[0254] Next, at a temperature of 25°C, a constant current charge and discharge of 0.2C is performed with a battery voltage between 4.20-3.00V, and the discharge capacity at this time is defined as C0. Thereafter, CC-CV charging is performed at a constant current of 0.2C in the same manner, and discharge is performed at a constant current of 2.0C until 3.0V is achieved at a temperature of 25°C, and the discharge capacity at this time is defined as C1. Then, as a rate characteristic, the capacity change rate represented by ΔC = (C1 / C0) × 100 (%) is obtained and evaluated according to the following criteria. The larger the value of the capacity change rate ΔC, the higher the discharge capacity and the lower the internal resistance.

[0255] A: Capacity change rate ΔC is 75% or more

[0256] B: Capacity change rate ΔC is 73% or more and less than 75%

[0257] C: Capacity change rate ΔC is 70% or more and less than 73%

[0258] D: Capacity change rate ΔC is less than 70%

[0259] (Example 1)

[0260] <Preparation of Granular Polymer A>

[0261] [Core forming process]

[0262] 100 parts of ion exchange water were placed in a 1 L flask with a septum and a stirrer, the gas phase was replaced with nitrogen, the temperature was raised to 80°C, and 0.3 parts of ammonium persulfate (APS) as a polymerization initiator was dissolved in 5.7 parts of ion exchange water and added.

[0263] On the other hand, in another container, 40 parts of ion exchange water, 0.18 parts of sodium polyoxyethylene alkyl ether sulfate (Kao Chemical Co.. Ltd., "LATEMUL E-118B") as an emulsifier, and 40.50 parts (40.5% in the core) of n-butyl acrylate as a (meth)acrylate monomer, 55.10 parts (55.1% in the core) of methyl methacrylate, 4.00 parts (4.0% in the core) of methacrylic acid as an acid group-containing monomer, and 0.40 parts (0.4% in the core) of allyl methacrylate as a crosslinking monomer were mixed to obtain a monomer composition. The monomer composition was continuously added to the above-mentioned 1L flask with a septum over 1 hour to perform polymerization. During the addition, the reaction was carried out at 80°C. After the addition was completed, stirring was further performed at 80°C for 1 hour to terminate the reaction.

[0264] [Shell Forming Step]

[0265] Next, the following monomer composition was added to the polymerization system within 2 minutes, the monomer composition comprising 15.6 parts (78% in the shell) of n-butyl acrylate and 3.4 parts (17% in the shell) of methyl methacrylate as (meth)acrylate monomers, 0.52 parts (2.6% in the shell) of acrylic acid as an acid group-containing monomer, 0.40 parts (2% in the shell) of hydroxyethyl acrylate as a hydroxyl group-containing monomer, and 0.08 parts (0.4% in the shell) of allyl methacrylate as a crosslinking monomer. After the addition was completed, the temperature was raised to 80° C. to allow the reaction to proceed for 3 hours. The aqueous dispersion containing the particulate polymer A thus obtained was cooled to 30° C. or less.

[0266] Here, an appropriate amount of N-methyl-2-pyrrolidone (NMP) as an organic solvent is added to a portion of the aqueous dispersion containing the granular polymer A, and after obtaining a mixture, a reduced pressure distillation is performed at 90°C to remove water from the mixture to obtain an NMP dispersion of the granular polymer A. The NMP dispersion of the granular polymer A is applied to a polytetrafluoroethylene sheet and dried for 3 to 8 hours under an environment of a temperature of 80 to 120°C to obtain a cast film. An ultrathin section of the obtained cast film is prepared, and the surface of the ultrathin section is measured in a tapping mode using an atomic force microscope (AFM), thereby obtaining a phase mapping image. Then, by observing the difference in elastic modulus in the obtained phase mapping image, it is confirmed that the granular polymer A is a granular polymer having a core-shell structure, and the core-shell structure has a core and a shell covering at least a portion of the outer surface of the core. The calculation results of the mass ratio of the shell in the granular polymer A and the measurement results of the glass transition temperature of the polymer of the core and shell of the granular polymer A are shown in Table 1.

[0267] <Preparation of Polymer B>

[0268] In a nitrogen atmosphere, 85 parts of ion exchange water and 0.2 parts of sodium dodecylbenzenesulfonate were added to a reactor A equipped with a mechanical stirrer and a condenser, and then heated to 55° C. while stirring, and 0.3 parts of potassium persulfate was prepared as a 5.0% aqueous solution and added to the reactor A. Next, in a nitrogen atmosphere, 93.0 parts of acrylonitrile as a cyano group-containing monomer, 1.0 part of acrylamide as an amide group-containing monomer, 2.0 parts of acrylic acid as an acid group-containing monomer, and 4.0 parts of n-butyl acrylate as a (meth)acrylate monomer, as well as 0.6 parts of sodium dodecylbenzenesulfonate, 0.035 parts of tert-dodecyl mercaptan, 0.4 parts of polyoxyethylene lauryl ether, and 80 parts of ion exchange water were added to a container B different from the above and equipped with a mechanical stirrer, and the mixture was stirred and emulsified to prepare a monomer mixed solution. Then, the monomer mixture was stirred and emulsified, and added to the reactor A at a constant rate over 5 hours to react until the polymerization conversion reached 95%, thereby obtaining an aqueous dispersion of a polyacrylonitrile copolymer (PAN1) mainly (93%) containing acrylonitrile units as polymer B. Using the obtained aqueous dispersion of polymer B, the properties of polymer B were measured. The results are shown in Table 1.

[0269] <Preparation of positive electrode binder composition>

[0270] The obtained aqueous dispersion of granular polymer A and aqueous dispersion of polymer B are mixed in such a manner that the content of polymer B is 80% relative to the total content of granular polymer A and polymer B, thereby obtaining an aqueous dispersion containing a binding material containing granular polymer A and polymer B. Then, an appropriate amount of N-methyl-2-pyrrolidone (NMP) as an organic solvent is added to the aqueous dispersion to obtain a mixture. Thereafter, reduced pressure distillation is performed at 90°C to remove water and excess NMP from the mixture to obtain a positive electrode binder composition (solid content concentration: 8%). Using the obtained positive electrode binder composition, the electrolyte swelling degree of the binding material contained in the positive electrode binder composition is measured. The results are shown in Table 1.

[0271] <Preparation of positive electrode slurry composition>

[0272] In a planetary mixer, 97 parts of NMC532 (Co-Ni-Mn lithium-containing composite oxide) as a positive electrode active material, 1.5 parts of acetylene black (manufactured by Denka Co., Ltd., trade name "HS-100") as a conductive material, and 1.5 parts (i.e., 1.5% of the solid content of the slurry composition) of the positive electrode binder composition obtained as described above were added and mixed, and then NMP as an organic solvent was slowly added, and the mixture was stirred and mixed at a temperature of 25±3°C and a rotation speed of 25 rpm. The viscosity at 25±3°C was 3600 mPa·s as measured by a B-type viscometer at 60 rpm (rotor M4).

[0273] <Manufacturing of positive electrode>

[0274] Use a notch wheel coater to coat at a rate of 21 ± 0.5 mg / cm 2 The positive electrode slurry composition obtained as described above was applied on an aluminum foil having a thickness of 20 μm as a current collector.

[0275] The slurry composition on the aluminum foil was dried by conveying it in an oven at 100°C for 2 minutes at a speed of 200 mm / min and then in an oven at 130°C for 2 minutes to obtain a positive electrode raw material having a positive electrode composite material layer formed on the current collector.

[0276] Subsequently, the positive electrode composite material layer side of the prepared positive electrode raw material was roll-pressed at a temperature of 25±3°C and a linear pressure of 14 t (tons) to obtain a positive electrode composite material layer with a density of 3.50 g / cm 3 The peel strength and resistance to powder removal of the positive electrode composite material layer were evaluated for the obtained positive electrode. The results are shown in Table 1.

[0277] <Preparation of Negative Electrode Binder Composition>

[0278] In a 5Mpa pressure-resistant container with a stirrer, 62 parts of styrene, 35 parts of 1,3-butadiene, 2 parts of itaconic acid, 1 part of 2-hydroxyethyl acrylate, 0.3 parts of tert-dodecyl mercaptan as a molecular weight regulator, 5 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion exchange water, and 1 part of potassium persulfate as a polymerization initiator were added. After sufficient stirring, the mixture was heated to a temperature of 55°C to initiate polymerization. The reaction was terminated by cooling when the monomer consumption reached 95.0%. A 5% sodium hydroxide aqueous solution was added to the aqueous dispersion containing the polymer thus obtained, and the pH was adjusted to 8. Thereafter, the unreacted monomers were removed by heating and reduced pressure distillation. Furthermore, the mixture was cooled to a temperature below 30°C, thereby obtaining an aqueous dispersion containing a binder for the negative electrode.

[0279] <Preparation of Negative Electrode Slurry Composition>

[0280] Add 48.75 parts of artificial graphite (theoretical capacity: 360 mAh / g) as a negative electrode active material, 48.75 parts of natural graphite (theoretical capacity: 360 mAh / g) and 1 part of carboxymethyl cellulose as a thickener in terms of solid content equivalent to a planetary mixer. Furthermore, dilute with ion exchange water so that the solid content concentration becomes 60%, and then mix at a rotation speed of 45 rpm for 60 minutes. Thereafter, add 1.5 parts of the above-obtained negative electrode binder composition in terms of solid content equivalent, and mix at a rotation speed of 40 rpm for 40 minutes. Then, add ion exchange water in a manner such that the viscosity becomes 3000±500 mPa·s (B-type viscometer, measured at 25°C and 60 rpm), thereby preparing a negative electrode slurry composition.

[0281] <Manufacturing of negative electrode>

[0282] Use a notch wheel coater to coat at a rate of 12.5 ± 0.5 mg / cm 2 The negative electrode slurry composition was applied to the surface of a copper foil having a thickness of 15 μm as a current collector in a manner. Thereafter, the copper foil coated with the negative electrode slurry composition was conveyed in an oven at a temperature of 80° C. for 2 minutes at a speed of 400 mm / min, and then conveyed in an oven at a temperature of 110° C. for 2 minutes, thereby drying the slurry composition on the copper foil to obtain a negative electrode raw material having a negative electrode composite material layer formed on the current collector.

[0283] Thereafter, the negative electrode material was roll-pressed at a linear pressure of 11 t (tons) at a temperature of 25 ± 3 °C to obtain a negative electrode material layer having a density of 1.60 g / cm 3 of the negative electrode.

[0284] <Preparation of Separator for Lithium Ion Secondary Battery>

[0285] A single-layer polypropylene spacer (manufactured by Celgard, “#2500”) was used.

[0286] <Manufacturing of lithium-ion secondary batteries>

[0287] Using the above-mentioned negative electrode, positive electrode and separator, a single-layer laminated battery (equivalent to an initial designed discharge capacity of 30 mAh) was prepared and placed in an aluminum packaging material. Thereafter, a 1.0 M LiPF6 solution (solvent: a mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) = 3 / 7 (volume ratio), additive: 2% by volume (solvent ratio) of vinylene carbonate) was filled as an electrolyte. Furthermore, in order to seal the opening of the aluminum packaging material, the aluminum packaging material was sealed by heat sealing at a temperature of 150°C to manufacture a lithium-ion secondary battery.

[0288] The rate characteristics were evaluated using this lithium ion secondary battery. The results are shown in Table 1.

[0289] (Examples 2 and 3)

[0290] The various operations, calculations, measurements, and evaluations were performed in the same manner as in Example 1 except that the composition of the monomer composition used in the shell portion forming step of the particulate polymer A was changed as shown in Table 1. The results are shown in Table 1.

[0291] (Examples 4 and 5)

[0292] When preparing the positive electrode binder composition, the various operations, calculations, measurements and evaluations were performed in the same manner as in Example 1 except that the content ratios of the particulate polymer A and the polymer B were changed as shown in Table 1. The results are shown in Table 1.

[0293] (Example 6)

[0294] The monomers used in the preparation of polymer B were changed to 65.0 parts of acrylonitrile as a cyano group-containing monomer, 1.0 parts of acrylamide as an amide group-containing monomer, 2.0 parts of acrylic acid as an acid group-containing monomer, and 32.0 parts of n-butyl acrylate as a (meth)acrylate monomer, thereby obtaining an aqueous dispersion of a polyacrylonitrile copolymer (PAN2) mainly (65%) containing acrylonitrile units as polymer B. Various operations, calculations, measurements and evaluations were performed in the same manner as in Example 1, except that the above-mentioned procedures were repeated. The results are shown in Table 1.

[0295] (Example 7)

[0296] The monomers used in preparing polymer B were changed to 2.0 parts of acrylic acid as an acid group-containing monomer, 38.0 parts of methyl methacrylate as a (meth)acrylate monomer, and 60.0 parts of n-butyl acrylate, thereby obtaining an aqueous dispersion of an acrylic copolymer as polymer B. Various operations, calculations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0297] (Comparative Examples 1 and 2)

[0298] The various operations, calculations, measurements, and evaluations were performed in the same manner as in Example 1 except that the composition of the monomer composition used in the shell portion forming step of the particulate polymer A was changed as shown in Table 1. The results are shown in Table 1.

[0299] (Comparative Example 3)

[0300] When preparing a positive electrode binder composition, after obtaining an aqueous dispersion containing a binder material including a particulate polymer A and a polymer B, the aqueous dispersion is directly used as a positive electrode binder composition without adding NMP as an organic solvent to prepare a positive electrode slurry composition. At this time, water is used instead of NMP as an organic solvent. In addition, various operations, calculations, measurements and evaluations are performed in the same manner as in Example 1. The results are shown in Table 1.

[0301] (Comparative Example 4)

[0302] The various operations, calculations, measurements, and evaluations were performed in the same manner as in Example 1 except that the polymer B was not used in preparing the positive electrode binder composition.

[0303] In addition, in Table 1 shown below,

[0304] "MMA" means methyl methacrylate,

[0305] "AA" stands for acrylic acid,

[0306] "HEA" means hydroxyethyl acrylate,

[0307] "AMA" stands for allyl methacrylate,

[0308] "BA" stands for n-butyl acrylate,

[0309] "MAA" means methacrylic acid,

[0310] "AN" stands for acrylonitrile,

[0311] "Aam" stands for acrylamide.

[0312] [Table 1]

[0313]

[0314] As can be seen from Table 1, in Examples 1 to 7 using a binder composition comprising a granular polymer A containing a core-shell structure and a polymer B having specified properties and an organic solvent, wherein the core-shell structure has a shell portion with a glass transition temperature within a specified range, it is possible to produce an electrode composite material layer having excellent peel strength and resistance to powder removal, as well as a lithium ion secondary battery that can exhibit high rate characteristics.

[0315] In addition, it can be seen that in Comparative Example 1 using a core-shell structured granular polymer having a shell portion with a glass transition temperature exceeding a specified range, although the lithium-ion secondary battery can exert high rate characteristics, the peel strength and resistance to powder removal of the electrode composite material layer are poor. On the other hand, it can be seen that in Comparative Example 2 using a core-shell structured granular polymer having a shell portion with a glass transition temperature not satisfying a specified range, although an electrode composite material layer with excellent peel strength and resistance to powder removal can be obtained, the rate characteristics of the lithium-ion secondary battery are poor.

[0316] Furthermore, it is found that in Comparative Example 3 in which water was used as a solvent instead of an organic solvent, the peel strength and powder removal resistance of the electrode composite material layer and the rate characteristics of the lithium ion secondary battery were poor.

[0317] Furthermore, it is found that in Comparative Example 4 using a binder containing only the core-shell structured particulate polymer A and not containing the polymer B having predetermined properties, the peel strength and powder removal resistance of the electrode composite material layer and the rate characteristics of the lithium ion secondary battery are poor.

[0318] Industrial Applicability

[0319] According to the present invention, it is possible to provide a binder composition for electrochemical element electrodes and a slurry composition for electrochemical element electrodes that can form an electrode composite material layer having excellent peel strength and powder removal resistance and enabling an electrochemical element to exhibit high rate characteristics.

[0320] Furthermore, according to the present invention, it is possible to provide an electrode for an electrochemical device having an electrode composite material layer which is excellent in peel strength and resistance to powder removal and which enables the electrochemical device to exhibit high rate characteristics.

[0321] Furthermore, according to the present invention, it is possible to provide an electrochemical device having the electrode and capable of exhibiting high-rate characteristics.

Claims

1. A binder composition for an electrochemical element electrode, comprising a binder material and an organic solvent, The bonding material comprises a particulate polymer A and a polymer B, The particulate polymer A has a core-shell structure including a core portion and a shell portion covering at least a portion of an outer surface of the core portion. The glass transition temperature of the polymer constituting the shell portion is -50°C or higher and 20°C or lower, The polymer B is mixed with the organic solvent at a concentration of 8 mass % to obtain a mixed solution at a shear rate of 1 s -1 The viscosity at that time is 100 mPa·s or more and 10000 mPa·s or less.

2. The binder composition for electrochemical element electrodes according to claim 1, wherein The content ratio of the polymer B in the binder is 60 mass % or more and 95 mass % or less.

3. The binder composition for electrochemical element electrodes according to claim 1 or 2, wherein The polymer B contains cyano group-containing monomer units in a ratio of 60% by mass or more.

4. The binder composition for electrochemical element electrodes according to claim 1 or 2, wherein The polymer constituting the core portion contains a crosslinkable monomer unit at a ratio of 0.01% by mass or more and 4.00% by mass or less.

5. The binder composition for electrochemical element electrodes according to claim 1 or 2, wherein The mixed solution obtained by mixing the bonding material with the organic solvent at a concentration of 8 mass % is subjected to a shearing speed of 1 s -1 The viscosity is 5000 mPa·s or more. 6 . A slurry composition for electrochemical element electrodes, comprising an electrode active material and the binder composition for electrochemical element electrodes according to claim 1 . 7 . An electrochemical element electrode comprising an electrode composite material layer formed using the slurry composition for an electrochemical element electrode according to claim 6 . 8 . An electrochemical device comprising the electrode for an electrochemical device according to claim 7 .